2022
DOI: 10.1021/acsami.2c03173
|View full text |Cite
|
Sign up to set email alerts
|

Revealing a Highly Sensitive Sub-ppb-Level NO2 Gas-Sensing Capability of Novel Architecture 2D/0D MoS2/SnS Heterostructures with DFT Interpretation

Abstract: In this work, we use a chemical method to design novel 2D-material/0D-quantum dot (MoS2/SnS) heterostructures. Furthermore, the unique 2D/0D heterostructure enhanced the NO2 gas-sensing capability 3 times and increased the sensing recoverability by more than 90%. Advanced characterization tools such as SEM, TEM, XRD, and AFM confirm the formation of MoS2/SnS heterojunction nanomaterials. Using AFM data, the average thickness of the MoS2 layer was found to be 5 nm. The highest sensor response of 0.33 with good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…66 In the metallopolymeric system, there is contact between them because the W atom is in the WS 2 and the –OH functional group is in the PVOH matrix. There are certain electronic parameters, such as HOMO–LUMO gap (Δ E ), electron affinity (EA), ionization potential (IP), electronegativity ( μ ), chemical potential ( χ ), chemical hardness ( η ), chemical softness ( σ ), and nucleophilicity index ( ω ), which can be calculated by relations (17)–(24), 67–69 to investigate the properties of the metallopolymeric system as presented in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…66 In the metallopolymeric system, there is contact between them because the W atom is in the WS 2 and the –OH functional group is in the PVOH matrix. There are certain electronic parameters, such as HOMO–LUMO gap (Δ E ), electron affinity (EA), ionization potential (IP), electronegativity ( μ ), chemical potential ( χ ), chemical hardness ( η ), chemical softness ( σ ), and nucleophilicity index ( ω ), which can be calculated by relations (17)–(24), 67–69 to investigate the properties of the metallopolymeric system as presented in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…The SDD basis set, which combines DZ and the Stuttgary-Dresden ECP basis set for improved reliability and precision, might lessen the burden of the large number of electrons in f-block elements. Various parameters such as the HOMO–LUMO gap, ionization potential electron affinity, and electronegativity have been calculated by using the energy of higher occupied molecular orbitals (HOMOs) and lower unoccupied molecular orbitals (LUMOs) according to the information presented in our prior articles. …”
Section: Methodsmentioning
confidence: 99%
“…The results showed that doping with B, N, or Al can greatly improve GQD's adsorbing capabilities and they serve as a promising application towards NO 2 gas sensing. Kumar et al, 94 designed a novel 2D-material/0Dquantum dot (MoS 2 /SnS) heterostructure with highly sensitive subppb-level NO 2 gas-sensing capability. The structure showed 3 times enhanced NO 2 gas-sensing capability and recovery increase by more than 90%.…”
Section: Quantum Dots (Qds)mentioning
confidence: 99%